Religion in Gosforth, 1951–2011: A Sociology Classic Revisited. (5th September 2013) - Bruce, Steve
Abstract : In The Sociology of an English Village: Gosforth, W. M. Williams described the religious life of rural Cumbria in the early 1950s. This research updates that study. Data on various indices of church and chapel involvement show the disappearance of communal conformity to the Church and increased commitment from the smaller core of committed members. The changed status of the Church is discussed as is its continuing role as occasional representative of the parish at large.